Effects of temperature acclimation on electrical properties of earthworm giant axons - Dierolf, B.M.; McDonald, H.S. (Zeitschrift für Vergleichende Physiologie, 1969)
1. The effects of temperature acclimation on electrical properties of earthworm axons (Lumbricus terrestris) were studied using intracellular stimulating and recording techniques. 2. Cold acclimation, compared to warm acclimation, was associated with decreased action potential duration and cable input resistance and increased maximum rate of rise and decline of the action potential and increased excitation threshold. In each case the direction of change occurring during acclimation to 5° C was opposite to that occurring immediately after cooling to 5° C, i.e., the acclimation changes were compensatory. 3. The significance of these changes is discussed with regard to their influence on over-all nerve function after thermal acclimation. © 1969 Springer-Verlag.
21 citations (Crossref) [2023-10-31]
Keywords: dept.bio

Paracoccidioides brasiliensis recovered from the intestinal tract of three bats (artibeus lituratus) in Colombia, S.A. - Grose, E.; Tamsitt, J.R. (Medical Mycology, 1965)
A total of 243 bats belonging to six species were collected in the tropical zone of west central Colombia. Three individuals of Artibeus lituratus (2 males and 1 female) from Melgar, Colombia, harboured Paracoccidioides brasiliensis; cultures being taken directly from the intestinal tract. To our knowledge this is the first report of recovery of P. brasiliensis from animals. © 1965 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.
54 citations (Crossref) [2023-10-31]
Keywords: Animal; Blastomycosis; Chiroptera; Colombia; Intestinal Diseases; Parasitic; animal; animal disease; article; bat; blastomycosis; dept.bio; intestine infection

A correlation of seedling height and chromosomal damage in irradiated barley seeds - Conger, Alan D; Stevenson, Harlan Q (Radiation Botany, 1969)
The most commonly used measurement of radiation damage to seeds is seedling height, the mean height a lot of seeds attains at some time during exponential growth. If planted immediately post-irradiation, seeds of a dose lot give a normal height distribution, but if stored before planting give very abnormal and even bimodal height distributions. By within-seed comparisons of chromosome abnormality (from roots excised at 24-36 hr) with height (attained by 7-9 days) in irradiated barley seeds, it is shown that damage to height and to chromosomes are closely correlated, even within a treatment in which great heterogeneity occurs. The two effects have equal radiosensitivity, but different shoulders to their dose curves. Seedling height is not depressed until 25-30 per cent of the cells bear chromosomal abnormalities. The heterogeneity observed is not due to a between-seed heterogeneity in dose or in oxygen content, and probably not in moisture. These experiments show that the heterogeneity arises from factors that operate on post-irradiation (indirect) storage damage, but are without effect on during-irradiation damage (direct). © 1969 Pergamon Press Ltd.
21 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-909-794-378-407 tex.type: [object Object]
Keywords: dept.bio

Special book review pesticides and the living landscape - Collins, Stephen (BioScience, 1964)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-936-491-371-936 tex.type: [object Object]
Keywords: dept.bio